Silicon nitride high-thermal-conductivity insulating composite material and preparation method thereof
Nanosilicon nitride and montmorillonite were treated by surface modification coupling agent, combined with homopolyformaldehyde paste resin, silicon nitride fibers and modified inorganic fillers, and the thermal conductivity of the busbar trough insulating plate was solved by heating and pressurizing molding. The problem of difficult to balance performance and mechanical properties has achieved a balance of high thermal conductivity and bending strength, and improved the durability and safety of the equipment.
Patent Information
- Application Number
- CN202411383937.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The thermal conductivity and mechanical properties of the existing bus trough insulating plates are difficult to take into account, which leads to excessive temperature, durability and safety problems at the joints, and the sintering and forming process is high energy consumption and costly.
Nanosilicon nitride and montmorillonite were treated with surface modification coupling agent, combined with homopolyformaldehyde paste resin, silicon nitride fibers and modified inorganic fillers, and formed a highly thermally conductive insulating composite material by heating and pressurization, optimizing nanometers The mass ratio of silicon nitride and montmorillonite is proportional to the resin mixture, which improves the interface binding force and thermal conductivity.
It achieves both high thermal conductivity and bending strength of the material, improves fracture toughness and dielectric properties, reduces manufacturing difficulty and cost, solves the problem of excessive joint temperature, and improves the durability and safety of the equipment.
Smart Images

Figure CN119264597A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermally conductive insulating materials, and specifically relates to a silicon nitride high thermal conductive insulating composite material and a preparation method thereof. Background Art
[0002] The bus duct connector is an adapter that connects the upper and lower bus ducts and distribution cabinets as the channel part of the bus system. It is generally composed of a connection cover connected by nuts and a multi-layer copper busbar inside the connection cover. The copper busbar is installed with an insulating plate and forms electrical insulation so that the bus duct busbar can be connected to the adjacent copper busbars for electrical connection. Since the connection between the connector and the bus duct will introduce contact resistance, a large amount of heat is generated when the current passes through the joint. When the temperature at the joint accumulates too high and cannot be dissipated, the high contact resistance and heat may reduce the efficiency of the bus duct system, and even affect the durability and safety of the bus duct, leading to fire risks. Therefore, improving the thermal conductivity and dielectric properties of the insulating plate material is of great significance to improving the safety and transmission performance of the bus system.
[0003] The high thermal conductivity insulation materials of existing bus duct insulation plates are generally ceramic-based or aluminum-based materials, with a thermal conductivity of only about 0.3W / m·k. In order to further improve the thermal conductivity of the material, thermal conductive fillers such as boron nitride, graphite, carbon nanotubes, and silicon nitride are further added to the material system. Silicon nitride (Si 3 N 4 ) As a material that is resistant to oxidation at high temperatures, can resist thermal shock, and has good thermal shock resistance, adding it to the material is also beneficial to improving the material's high dielectric constant and low dielectric loss properties, such as:
[0004] Patent CN112661518B discloses a high thermal conductivity silicon nitride ceramic insulating board and its preparation method. After silicon nitride powder is mixed with a variety of sintering aids, solvents and binders to make pulp, it is granulated, pressed, debinded and sintered to form, which can achieve high bending strength and thermal conductivity. However, the solid content in the material is large, and it is easy to crack or crack when subjected to large compressive stress and thermal expansion stress. The fracture toughness, dielectric properties and stability are not good. At the same time, long-term high-temperature sintering is required, and the production energy consumption and cost are high. Therefore, the manufacture of silicon nitride insulating composite materials with excellent thermal conductivity, better electrical insulation performance and insulation material toughness, and simpler preparation methods still have the following technical difficulties:
[0005] 1. PC, epoxy resin and other resin-based materials have good mechanical properties, high temperature resistance and electrical insulation properties, and can make the material size more stable, which is beneficial to reducing the difficulty of processing, but the thermal conductivity is relatively poor. When silicon nitride is used as a thermal conductive additive, the silicon nitride particles have high surface energy, poor dispersibility and compatibility, which will increase the interface voids, cause the thermal resistance of the interface between the matrix particles and the matrix, and reduce the thermal conductivity and thermal stability of the composite material. In order to improve the dispersion performance, reducing the silicon nitride content will also lead to the loss of thermal conductivity of the material.
[0006] Second, using silicon nitride fillers with smaller particle sizes can improve the thermal conductivity of the material, but the filling amount and thermal contact surface of silicon nitride of a single particle size are limited, resulting in limited efficiency in heat transfer. Further increasing the filling amount of thermal conductive fillers will not only have limited improvement in the thermal conductivity of the material, but will also lead to mechanical deterioration of the material and a significant decrease in fracture toughness, which will lead to cracks or cracking, further affecting heat dissipation performance and safety.
[0007] 3. Although polymer insulating materials such as epoxy resin have good dielectric properties, a small amount of decomposition or nucleation will occur during high-temperature processing, affecting the color of the product. At the same time, as the manufacturing temperature increases, it will become a stress concentration point when the crystallinity is high, resulting in increased notch sensitivity, impact toughness and molding shrinkage, which is not conducive to improving the bending strength and fracture toughness of the insulating material. Cracks will affect the insulation, and then affect the normal use and safety of the equipment. Summary of the invention
[0008] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a silicon nitride high thermal conductivity insulating composite material and a preparation method thereof, which can reduce the manufacturing difficulty and cost, take into account the high thermal conductivity and bending strength of the material, and further improve the fracture toughness and dielectric properties of the composite material, thereby effectively solving the problem of high temperature at the bus duct joint due to large resistance, and improving the durability and safety of the equipment.
[0009] The technical solution adopted by the present invention to solve its technical problem is:
[0010] A method for manufacturing a silicon nitride high thermal conductivity insulating composite material, the manufacturing method comprising:
[0011] Step 1: using a surface modification coupling agent to perform surface modification on nano silicon nitride and montmorillonite to obtain a modified inorganic filler, wherein the mass ratio of nano silicon nitride to montmorillonite is (4-7): (1-2);
[0012] Step 2: homopolyformaldehyde, initiator, antioxidant and release agent are mixed into a paste resin, silicon nitride fiber and modified inorganic filler are added into the paste resin and mixed into a resin mixture, wherein the mass ratio of the paste resin, silicon nitride fiber and modified inorganic filler is (1-2): (1-2): (3-8);
[0013] Step 3: Add the resin mixture into the preheated mold, heat and pressurize at 175-210° C. until it is cured and formed, and then demold to obtain a finished composite insulating material.
[0014] In the above manufacturing method:
[0015] Nano silicon nitride (Si 3 N 4 ) is a nanomaterial that is resistant to oxidation at high temperatures, can resist thermal shock, and has good thermal shock resistance. Adding it to the material is also beneficial to improving the material's high dielectric constant and low dielectric loss characteristics. Montmorillonite, as an inorganic silicate with a natural nanostructure, can improve the toughness and heat resistance of the composite material. With the increase of the montmorillonite content, the material toughness and product dimensional stability are improved. Further surface modification coupling agent treatment of nano silicon nitride and montmorillonite can be used to coat and improve the compatibility of inorganic fillers with paste resins, improve interfacial bonding, reduce the thermal resistance of the interface between matrix particles and the matrix, increase the thermal conductivity of the composite material, avoid agglomeration, reduce material voids, achieve high filling, and enable the dispersed improved inorganic filler to produce good stress transfer with the matrix interface, thereby improving the mechanical properties and processing properties of the product, and comprehensively improving the thermal stability, thermal conductivity and fracture toughness of the composite material. Therefore, the preferred mass ratio of nano silicon nitride to montmorillonite is (4~7): (1~2).
[0016] Compared with epoxy resin, ABS resin, PC and other polymer insulating thermoplastic materials, homopolymer has better thermal conductivity among thermoplastics or thermosetting plastics and better dielectric properties, which is beneficial to improve the thermal conductivity of composite insulating materials with inorganic modified fillers and silicon nitride fibers. At the same time, the processing and production of homopolymer is easier and simpler, and it has the advantages of ductility, fatigue resistance, mechanical strength, very small creep, and flame retardancy, especially rigidity and strength. It is beneficial to replace sintering processing by heating and pressure molding, reducing processing difficulty and cost. Antioxidants are used to inhibit the decomposition and nucleation of homopolymer during high-temperature processing. The addition of release agents is used to improve the demoulding performance of the product after curing, eliminate mold deposits, and improve productivity. Effective bonding is established through initiators, but the crystallinity of homopolymer is high and the crystallization rate is fast during the processing of homopolymer, while the heat transfer of nano-silicon nitride is limited:
[0017] On the one hand, the thermal conductivity of the material is further improved by using a paste resin of homopolymer formaldehyde with excellent performance as the matrix and modified inorganic fillers and silicon nitride fibers. Compared with the filling amount of silicon nitride with a single particle size, the silicon nitride can be stacked more densely, forming a hierarchical structure of different sizes inside the material, so that a bridging effect is formed between nano silicon nitride, montmorillonite and silicon nitride fibers, effectively increasing the thermal conductive network chain, thereby improving the thermal conductivity, compensating for the loss of thermal conductivity caused by reducing the content of granular silicon nitride, and improving the dispersion performance of the modified inorganic filler, which is beneficial to improving the dielectric properties. It is more suitable for curing and molding by heating and pressurizing to reduce the manufacturing difficulty and cost.
[0018] On the other hand, in order to reduce the adverse effects of crystallization as stress concentration on toughness, the resin mixture can be compounded with silicon nitride fiber through the paste resin of homopolymer formaldehyde to increase the load to be borne. Silicon nitride fiber can effectively disperse stress and fill microcracks in the material, thereby improving the tensile strength and fracture toughness of the material. At the same time, by compounding with inorganic improved fillers and silicon nitride fiber, the increase in shrinkage due to increased crystallinity can be avoided, which is beneficial to improving the molding dimensional accuracy.
[0019] The design basis of the ratio of the resin mixture includes: the paste resin can maintain the thermal conductivity and insulation of the material, but if the content is too low, the processing performance will be poor, and if the content is too high, the price will be high, the difficulty of production will increase, and a certain degree of thermal conductivity loss will be caused; as the content of the improved inorganic filler increases, the molecular spacing in the homopolymer increases, the dipole tendency of the polar groups in the composite material increases, the dielectric constant can be increased, and then the insulation performance at high temperature can be improved, but if the content of the improved inorganic filler is too high, it will also increase the nucleation effect, form large spherulites, increase the notch sensitivity of the product, and cause the molding shrinkage rate to increase, which is not conducive to reducing the manufacturing difficulty of the composite material; silicon nitride fiber can increase the toughness and thermal conductivity of the material, but if the ratio is too low, the toughness improvement is limited, but if the ratio is too high, the composite material will not be dense enough, resulting in a decrease in thermal conductivity, so the preferred mass ratio of the paste resin, silicon nitride fiber and modified inorganic filler is (1-2): (1-2): (3-8).
[0020] Compared with sintering manufacturing, heating and pressure molding does not require processing at thousands of degrees and can be formed in a short time, which is conducive to improving processing efficiency, reducing processing difficulty and cost. At the same time, due to the sensitivity of homopolymer to temperature, further controlling the heating temperature during the heating process can avoid decomposition and improve the mechanical properties of the composite material.
[0021] In a preferred embodiment, the surface modification coupling agent is one or more of phthalate coupling agent KR-12, long-chain silane coupling agent KH-3116 or silane coupling agent ZJ-308. The selection criteria of the surface modification coupling agent include: phthalate coupling agent KR-12 as a phthalate coupling agent can reduce the viscosity of the system, has good dispersion and anti-settling effects, has good compatibility with polar polymers for inorganic fillers, and is beneficial for reducing the modification temperature and processing time; silane coupling agent KH-3116 as a long-chain silane coupling agent, is soluble in organic matter, and is used for surface modification of inorganic ultrafine powders, which can improve their compatibility with organic matter, and is beneficial for increasing the mechanical properties and packaging properties of reinforced products; silane coupling agent ZJ-308 as a monofunctional silane, has high reactivity, and can chemically adsorb with nano silicon nitride and montmorillonite through hydrophilic groups to change the surface and reduce viscosity.
[0022] The amount of the surface modification coupling agent is set according to the comparative area of nano silicon nitride and montmorillonite. In a preferred embodiment, the mass of the surface modification coupling agent is 4.5% to 8% of the total mass of nano silicon nitride and montmorillonite.
[0023] In a preferred embodiment, the surface modification method of nano silicon nitride and montmorillonite in step 1 comprises:
[0024] The surface modified coupling agent and the solvent are heated and mixed, nano silicon nitride and montmorillonite are added, and then stirred and refluxed at 40-80°C for 1-2 hours, and the refluxed substrate is subjected to high-speed centrifugation and washing, and then dried to obtain the modified inorganic filler.
[0025] In the surface modification process of nano silicon nitride and montmorillonite, the solvent is preferably dimethylformamide (DMF) or ethanol, which can further control the stirring reflux temperature and promote the nano silicon nitride and montmorillonite to be evenly dispersed in the surface modification coupling agent and fully react. Too high or too low temperature can easily lead to coupling agent failure or too slow reaction rate.
[0026] In a preferred embodiment, the initiator is one or a combination of organic peroxides TBPO and TBEC. The organic peroxides TBPO and TBEC can act synergistically to initiate coupling by splitting peroxy groups into free radicals.
[0027] In a preferred embodiment, the mass of the initiator is 0.1% to 0.5% of the mass of the homopolyoxymethylene.
[0028] In a preferred embodiment, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168. The selection criteria of the antioxidant include: antioxidant 1010 and antioxidant 1076, as a high molecular weight hindered phenol antioxidant, have the advantages of high thermal stability, long lasting effect, no coloring, no pollution, and non-toxicity, and have good compatibility with homopolyformaldehyde. Antioxidant 168, as a phosphite antioxidant, can improve the thermal stability of homopolyformaldehyde during thermal processing and reduce corrosion to the mold. Antioxidant 1010 or antioxidant 1076 has a significant synergistic effect with antioxidant 168, can effectively prevent the thermal oxidative degradation of homopolyformaldehyde under heating and pressurization, and can improve the discoloration resistance of the composite material under high temperature processing conditions.
[0029] In a preferred embodiment, the weight of the antioxidant is 0.1% to 0.2% of the weight of the homopolyoxymethylene.
[0030] In a preferred embodiment, the release agent is one or both of zinc stearate and ethylene bis stearic acid amide. Among the release agents, zinc stearate has the advantages of good heat resistance and good stress resistance, and ethylene bis stearic acid amide has the advantages of good temperature resistance and good lubrication performance for homopolyformaldehyde, which can improve the fluidity of the paste resin and the dispersibility and coupling of silicon nitride fiber and modified inorganic filler in the paste resin. The mixture of zinc stearate and ethylene bis stearic acid amide has a good synergistic effect.
[0031] In a preferred embodiment, the mass of the release agent is 3% to 5% of the mass of the homopolyoxymethylene.
[0032] In a preferred embodiment, in the step 2, homopolyformaldehyde, initiator, antioxidant and release agent are stirred at 30-50°C.
[0033] In a preferred embodiment, the silicon nitride fiber has a diameter of 5 to 15 microns and a length of 4 to 8 mm.
[0034] In the step three, if the pressurization pressure is too high or too low, it will affect the crystal phase composition, density and mechanical properties of the final product. In a preferred embodiment, the preheating temperature of the mold is 150-175° C. and the pressurization is 17-30 MPa.
[0035] A silicon nitride high thermal conductivity insulating composite material, wherein the composite material is manufactured by any one of the above-mentioned methods for manufacturing a silicon nitride high thermal conductivity insulating composite material.
[0036] The use of the silicon nitride high thermal conductivity insulation composite material is characterized in that the silicon nitride high thermal conductivity insulation composite material is used to manufacture an insulation board of a bus duct connector, and the bending strength of the insulation board is greater than 395MPa and the fracture toughness is greater than 10MPa / m0.5 , thermal conductivity>25W / m·k, volume resistivity>10 13 Ω·cm.
[0037] Compared with the prior art, the beneficial effects of the present invention are at least:
[0038] (1) The present invention uses a paste resin of homopolyformaldehyde with better thermal conductivity as an insulating matrix, and uses a surface modification coupling agent to modify the surface of nano silicon nitride and montmorillonite, which can be coated to improve the compatibility between the inorganic filler and the paste resin and improve the interface bonding force. On the one hand, the nano silicon nitride in the modified inorganic filler is used to improve the dielectric properties of the material, achieve high filling, and give full play to the thermal conductivity; on the other hand, the modified nano silicon nitride and montmorillonite work together to enable the dispersed improved inorganic filler to produce good stress transfer with the matrix interface, improve the mechanical properties and fracture toughness of the material, and at the same time increase the molecular distance in the homopolyformaldehyde and increase the dipole tendency of the polar groups in the composite material, thereby improving the insulation performance at high temperature and solving the problem that it is difficult to balance the dielectric properties, thermal conductivity and mechanical properties of the material.
[0039] (2) The paste resin of the present invention is compounded with modified inorganic filler and silicon nitride fiber. Compared with silicon nitride filler with a single particle size, on the one hand, modified nano-scale particles and fibrous silicon nitride are added to form a hierarchical structure of different sizes inside the material, making the stacking of silicon nitride more compact, effectively increasing the thermal conductive network chain, and compensating for the loss of thermal conductivity caused by reducing the content of granular silicon nitride; on the other hand, the silicon nitride fiber effectively disperses stress, improves the tensile strength and fracture toughness of the material, avoids the increase of shrinkage due to increased crystallinity, is beneficial to improving the molding dimensional accuracy, and solves the problem of difficulty in taking both thermal conductivity and high fracture toughness into consideration.
[0040] (3) The components of the present invention are relatively simple. Compared with sintering manufacturing, the present invention is more suitable for the processing of homopolymer with higher temperature sensitivity. It can be formed in a short time at a lower temperature, and an initiator can be used to build effective bonds. An antioxidant can be used to inhibit the decomposition and nucleation of homopolymer during high-temperature processing. A release agent can be used to improve the demolding performance of the product after curing, which is beneficial to improving processing efficiency, reducing processing difficulty and cost, and can further improve the fracture toughness of the composite material, improve industrial adaptability, and effectively solve the problem of high temperature caused by large resistance at the bus duct joint, thereby improving the durability and safety of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0042] Figure 1 This is a sample diagram of Example 1 of the present invention. DETAILED DESCRIPTION
[0043] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0044] The sources of reagents used in the following examples and comparative examples include:
[0045] Phthalate coupling agent KR-12: isopropyl tri(dioctylphosphoyl) titanate; long-chain silane coupling agent KH-3116: hexadecyltrimethoxysilane; silane coupling agent ZJ-308: n-octyltriethoxysilane; purchased from Guangzhou Zhongjie Chemical Technology Co., Ltd.
[0046] Nano silicon nitride: 20 nm, purchased from Shanghai Yaotian New Material Technology Co., Ltd.; silicon nitride fiber with a diameter of 5 to 15 microns and a length of 4 to 8 mm, purchased from Shandong Stari Metal Materials Co., Ltd.
[0047] 23P homopolyoxymethylene, POM, was purchased from Jiangsu Yican Special Plastic Co., Ltd.
[0048] Antioxidant 1010: pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; Antioxidant 1076: octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; Antioxidant 168: purchased from Dongguan Xingyuan Chemical Co., Ltd.
[0049] Organic peroxide TBPO: tert-butyl peroxy 2-ethylhexanoate, organic peroxide TBEC: tert-butyl peroxy 2-ethylhexyl carbonate, were purchased from Jiangyin Wanqian Chemicals Co., Ltd.
[0050] Zinc stearate was purchased from Changzhou Deshuo Chemical Technology Co., Ltd., and ethylene bisstearamide EB-FF was purchased from Shanghai Yunhe Material Technology Co., Ltd.
[0051] In the following embodiments and comparative examples, the bending strength of the composite insulating material is tested according to the ASTMD790 standard, the fracture toughness is tested according to the ASTMD638 standard, the thermal conductivity is tested according to the ASTMD5470 standard, and the volume resistivity is tested according to the ASTMD257 standard; the bus duct test method is: according to the industry specification JB / T9662-2001 "Dense Insulation Bus Trunk System" test standard, the bus duct temperature rise test uses a test device to pass the rated current into the bus duct, the end is short-circuited to form a loop, the joint is tightened with an insulating plate and a connector with bolts according to the standard torque, a temperature sensor is arranged at the joint, and the temperature rise curve is recorded. Within the standard time, the temperature tends to be stable and the temperature rise limit does not exceed the standard maximum value, that is, ≤70k is qualified.
[0052] Embodiment 1:
[0053] A preferred embodiment of the method for manufacturing the silicon nitride high thermal conductivity insulating composite material of the present invention comprises:
[0054] Step 1: Use a surface modification coupling agent to modify the surface of nano silicon nitride and montmorillonite to obtain a modified inorganic filler:
[0055] The surface modified coupling agent and the solvent are heated and mixed, nano silicon nitride and montmorillonite are added, and the mixture is stirred and refluxed at 60° C. for 1.5 hours, and the refluxed substrate is subjected to high-speed centrifugation, and the centrifuged substrate is washed with the solvent for 3 times, and then dried to obtain a modified inorganic filler;
[0056] The surface modification coupling agent is composed of phthalate coupling agent KR-12 and silane coupling agent ZJ-308 in a mass ratio of 1:1. The mass of the surface modification coupling agent is 6% of the total mass of nano silicon nitride and montmorillonite. The solvent is dimethylformamide (DMF); the mass ratio of nano silicon nitride to montmorillonite is 5:1.5.
[0057] Step 2: homopolyformaldehyde, initiator, antioxidant and release agent are stirred evenly at 40° C. and blended into a paste resin. Silicon nitride fiber and the modified inorganic filler obtained in step 2 are evenly added to the paste resin in 5 batches and mixed into a resin mixture. The mass ratio of the paste resin, silicon nitride fiber and modified inorganic filler is 1.5:1.5:5.
[0058] The initiator is organic peroxide TBPO, and the mass of the initiator is 0.2% of the mass of homopolyformaldehyde; the antioxidant is antioxidant 1010, and the mass of the antioxidant is 0.15% of the mass of homopolyformaldehyde; the release agent is ethylene bis stearic acid amide, and the mass of the release agent is 4% of the mass of homopolyformaldehyde.
[0059] Step 3: Add the resin mixture obtained in step 2 into a preheated mold at a preheating temperature of 160°C, heat and pressurize to 25MPa at 185°C, and after curing and molding, demould to obtain a finished composite insulating material. Figure 1 shown.
[0060] The finished composite insulation material is used as the insulation board of the bus duct connector. The temperature rise limit at the joint meets the standard. When the joint is connected, the insulation board does not produce cracks or damage under the standard torque of 80N·M, indicating that it has good toughness and good contact with the busbar, which meets the requirements.
[0061] By setting the mass ratio of nano silicon nitride to montmorillonite different from that in Example 1, the influence of different mass ratios of nano silicon nitride to montmorillonite on the performance of the composite insulating material was investigated, and the results are shown in Table 1 below;
[0062] Table 1. Composite insulation materials with different mass ratios of nano-silicon nitride and montmorillonite
[0063]
[0064] As can be seen from Table 1, the increase in the proportion of nano-silicon nitride is beneficial to increasing the thermal conductivity of the composite material and improving the high dielectric constant and low dielectric loss characteristics of the material. The increase in the proportion of montmorillonite improves the toughness of the material and the dimensional stability of the product. In order to improve the mechanical properties and processing properties of the product and comprehensively improve the thermal stability, thermal conductivity and fracture toughness of the composite material, the preferred mass ratio of nano-silicon nitride to montmorillonite is (4-7): (1-2).
[0065] Embodiment 2:
[0066] A preferred embodiment of the method for manufacturing the silicon nitride high thermal conductivity insulating composite material of the present invention comprises:
[0067] Step 1: Use a surface modification coupling agent to modify the surface of nano silicon nitride and montmorillonite to obtain a modified inorganic filler:
[0068] The surface modified coupling agent and the solvent are heated and mixed, nano silicon nitride and montmorillonite are added, and the mixture is stirred and refluxed at 40° C. for 1 hour, the refluxed substrate is subjected to high-speed centrifugation, the centrifuged substrate is washed with the solvent for 3 times, and the modified inorganic filler is obtained after drying;
[0069] The surface modification coupling agent is composed of long-chain silane coupling agent KH-3116 and silane coupling agent ZJ-308 in a mass ratio of 1:1. The mass of the surface modification coupling agent is 4.5% of the total mass of nano silicon nitride and montmorillonite. The solvent is ethanol; the mass ratio of nano silicon nitride to montmorillonite is 4:2.
[0070] Step 2: homopolyformaldehyde, initiator, antioxidant and release agent are stirred evenly at 30° C. to form a paste resin, silicon nitride fiber and modified inorganic filler obtained in step 2 are added to the paste resin in 5 batches, and mixed to form a resin mixture, wherein the mass ratio of the paste resin, silicon nitride fiber and modified inorganic filler is 1:2:6;
[0071] The initiator is an organic peroxide TBEC, and the mass of the initiator is 0.1% of the mass of the homopolyformaldehyde; the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, and the mass of the antioxidant is 0.1% of the mass of the homopolyformaldehyde; the release agent is zinc stearate, and the mass of the release agent is 3% of the mass of the homopolyformaldehyde.
[0072] Step 3: Add the resin mixture obtained in step 2 into a preheated mold at a preheating temperature of 150° C., heat and pressurize to 30 MPa at 175° C., and after solidification, demoulding to obtain a finished composite insulating material.
[0073] The finished composite insulation material is used as the insulation board of the bus duct connector. The temperature rise limit at the joint meets the standard. When the joint is connected, the insulation board does not produce cracks or damage under the standard torque of 80N·M, indicating that it has good toughness and good contact with the busbar, which meets the requirements.
[0074] The silicon nitride fiber in Example 2 was replaced by glass fiber and quartz fiber respectively, and the effects of different fibers on the performance of the composite insulating material were investigated. The results are shown in Table 2 below:
[0075] Table 2. Composite insulation materials with different fibers
[0076]
[0077] From the comparison results of Example 2 with Comparative Examples 3 and 4, it can be seen that by adding modified nano-scale particles and fibrous silicon nitride, a hierarchical structure of different sizes can be formed inside the material, making the stacking of silicon nitride more compact, effectively increasing the thermal conductive network chain, and compensating for the loss of thermal conductivity caused by reducing the content of granular silicon nitride. At the same time, the stress can be effectively dispersed through the silicon nitride fiber, improving the tensile strength and fracture toughness of the material, avoiding the increase in shrinkage due to increased crystallinity, which is beneficial to improving the molding size accuracy and solving the problem of difficulty in taking both thermal conductivity and high fracture toughness into consideration.
[0078] Embodiment 3:
[0079] A preferred embodiment of the method for manufacturing the silicon nitride high thermal conductivity insulating composite material of the present invention comprises:
[0080] Step 1: Use a surface modification coupling agent to modify the surface of nano silicon nitride and montmorillonite to obtain a modified inorganic filler:
[0081] The surface modified coupling agent and the solvent are heated and mixed, nano silicon nitride and montmorillonite are added, and the mixture is stirred and refluxed at 80° C. for 2 hours, and the refluxed substrate is subjected to high-speed centrifugation, and the centrifuged substrate is washed with the solvent for 3 times, and then dried to obtain the modified inorganic filler;
[0082] The surface modification coupling agent is long-chain silane coupling agent KH-3116, the mass of the surface modification coupling agent is 8% of the total mass of nano silicon nitride and montmorillonite, the solvent is dimethylformamide (DMF), and the mass ratio of nano silicon nitride to montmorillonite is 7:1.
[0083] Step 2: homopolyformaldehyde, initiator, antioxidant and release agent are stirred evenly at 50° C. to form a paste resin, silicon nitride fiber and modified inorganic filler obtained in step 2 are added to the paste resin in 5 batches, and mixed to form a resin mixture, wherein the mass ratio of the paste resin, silicon nitride fiber and modified inorganic filler is 2:1:3;
[0084] The initiator is composed of organic peroxides TBPO and TBEC in a mass ratio of 1:1, and the mass of the initiator is 0.5% of the mass of the homopolyformaldehyde; the antioxidant is antioxidant 1076, and the mass of the antioxidant is 0.2% of the mass of the homopolyformaldehyde; the release agent is composed of zinc stearate and ethylene bis stearamide in a mass ratio of 1:1, and the mass of the release agent is 5% of the mass of the homopolyformaldehyde.
[0085] Step 3: Add the resin mixture obtained in step 2 into a preheated mold at a preheating temperature of 175° C., heat and pressurize the mold to 17 MPa at 210° C., and after curing and molding, demould to obtain a finished composite insulating material.
[0086] The finished composite insulation material is used as the insulation board of the bus duct connector. The temperature rise limit at the joint meets the standard. When the joint is connected, the insulation board does not produce cracks or damage under the standard torque of 80N·M, indicating that it has good toughness and good contact with the busbar, which meets the requirements.
[0087] The mass ratio of the paste resin, silicon nitride fiber and modified inorganic filler in Example 3 was replaced to investigate the effects of different mass ratios of the paste resin, silicon nitride fiber and modified inorganic filler on the performance of the composite insulating material. The results are shown in Table 3 below:
[0088] Table 3. Composite insulation materials with different mass ratios of paste resin, silicon nitride fiber and modified inorganic filler
[0089]
[0090] As can be seen from Table 3 above, the paste resin can maintain the thermal conductivity and insulation of the material, but too low a content will lead to poor processing performance, and a high content will cause a certain degree of thermal conductivity loss; with the increase of the content of the improved inorganic filler, the insulation performance at high temperature can be improved, but too high a content of the improved inorganic filler will also lead to increased nucleation, the formation of large spherulites, and increase the notch sensitivity of the product, causing an increase in the molding shrinkage rate, which is not conducive to reducing the manufacturing difficulty of the composite material; silicon nitride fiber can increase the toughness and thermal conductivity of the material, but if the ratio is too low, the toughness improvement is limited, but if the ratio is too high, the composite material will not be dense enough, resulting in a decrease in thermal conductivity. Therefore, the preferred mass ratio of the paste resin, silicon nitride fiber and modified inorganic filler is (1-2): (1-2): (3-8).
[0091] Embodiment 4:
[0092] A preferred embodiment of the method for manufacturing the silicon nitride high thermal conductivity insulating composite material of the present invention comprises:
[0093] Step 1: Use a surface modification coupling agent to modify the surface of nano silicon nitride and montmorillonite to obtain a modified inorganic filler:
[0094] The surface modified coupling agent and the solvent are heated and mixed, nano silicon nitride and montmorillonite are added, and the mixture is stirred and refluxed at 50° C. for 1.5 hours, the refluxed substrate is subjected to high-speed centrifugation, the centrifuged substrate is washed with the solvent for 3 times, and the modified inorganic filler is obtained after drying;
[0095] The surface modification coupling agent is phthalate coupling agent KR-12, the mass of the surface modification coupling agent is 7% of the total mass of nano silicon nitride and montmorillonite, the solvent is ethanol, and the mass ratio of nano silicon nitride to montmorillonite is 6:1.5.
[0096] Step 2: homopolyformaldehyde, initiator, antioxidant and release agent are stirred evenly at 45° C. to form a paste resin, silicon nitride fiber and modified inorganic filler obtained in step 2 are added to the paste resin in 5 batches, and mixed to form a resin mixture, wherein the mass ratio of the paste resin, silicon nitride fiber and modified inorganic filler is 1:1.5:8;
[0097] The initiator is composed of organic peroxides TBPO and TBEC in a mass ratio of 1:1, and the mass of the initiator is 0.3% of the mass of the homopolyformaldehyde; the antioxidant is composed of antioxidant 1076 and antioxidant 168 in a mass ratio of 1:1, and the mass of the antioxidant is 0.15% of the mass of the homopolyformaldehyde; the release agent is composed of zinc stearate and ethylene bis stearamide in a mass ratio of 1:1, and the mass of the release agent is 4% of the mass of the homopolyformaldehyde.
[0098] Step 3: Add the resin mixture obtained in step 2 into a preheated mold at a preheating temperature of 165° C., heat and pressurize the mold to 22 MPa at 200° C., and after curing and molding, demould to obtain a finished composite insulating material.
[0099] The finished composite insulation material is used as the insulation board of the bus duct connector. The temperature rise limit at the joint meets the standard. When the joint is connected, the insulation board does not produce cracks or damage under the standard torque of 80N·M, indicating that it has good toughness and good contact with the busbar, which meets the requirements.
[0100] The heating temperature in step 3 was changed to investigate the effect of different heating temperatures on the performance of the composite insulation material. The results are shown in Table 4 below:
[0101] Table 4. Composite insulation materials with different mass ratios of paste resin, silicon nitride fiber and modified inorganic filler
[0102]
[0103] It can be seen from Table 4 above that, compared with sintering manufacturing, the present invention is more suitable for homopolymer processing with higher temperature sensitivity, can be formed in a short time at a lower temperature, and can use an initiator to build effective bonds. During the heating process, further controlling the heating temperature can avoid decomposition and improve the mechanical properties of the composite material.
[0104] From the results of Examples 1 to 4, it can be seen that the use of silicon nitride high thermal conductivity insulation composite material for manufacturing the insulation board of the bus duct connector can achieve a bending strength of the insulation board greater than 395 MPa and a fracture toughness greater than 10 MPa / m 0.5 , thermal conductivity>25W / m·k, volume resistivity>10 13 Ω·cm, which can take into account the high thermal conductivity and flexural strength of the material, further improve the fracture toughness and dielectric properties of the composite material, and thus effectively solve the problem of high temperature at the bus duct joints caused by large resistance, and improve the durability and safety of the equipment.
[0105] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a silicon nitride high thermal conductivity insulating composite material, characterized in that: The manufacturing method thereof comprises: Step 1: using a surface modification coupling agent to perform surface modification on nano silicon nitride and montmorillonite to obtain a modified inorganic filler, wherein the mass ratio of nano silicon nitride to montmorillonite is (4-7): (1-2); Step 2: homopolyformaldehyde, initiator, antioxidant and release agent are mixed into a paste resin, silicon nitride fiber and modified inorganic filler are added into the paste resin and mixed into a resin mixture, wherein the mass ratio of the paste resin, silicon nitride fiber and modified inorganic filler is (1-2): (1-2): (3-8); Step 3: Add the resin mixture into the preheated mold, heat and pressurize at 175-210° C. until it is cured and formed, and then demold to obtain a finished composite insulating material.
2. The method for manufacturing the silicon nitride high thermal conductivity insulation composite material according to claim 1, characterized in that: The surface modification coupling agent is one or more of phthalate coupling agent KR-12, long-chain silane coupling agent KH-3116 or silane coupling agent ZJ-308, and the mass of the surface modification coupling agent is 4.5% to 8% of the total mass of nano silicon nitride and montmorillonite.
3. The method for manufacturing the silicon nitride high thermal conductivity insulation composite material according to claim 1, characterized in that: The surface modification method of nano silicon nitride and montmorillonite in step 1 comprises: The surface modified coupling agent and the solvent are heated and mixed, nano silicon nitride and montmorillonite are added, and then stirred and refluxed at 40-80°C for 1-2 hours, and the refluxed substrate is subjected to high-speed centrifugation and washing, and then dried to obtain the modified inorganic filler.
4. The method for manufacturing the silicon nitride high thermal conductivity insulation composite material according to claim 1, characterized in that: The initiator is one or a combination of organic peroxides TBPO and TBEC, and the mass of the initiator is 0.1% to 0.5% of the mass of the homopolyformaldehyde.
5. The method for manufacturing the silicon nitride high thermal conductivity insulation composite material according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168, and the mass of the antioxidant is 0.1% to 0.2% of the mass of homopolyoxymethylene.
6. The method for manufacturing the silicon nitride high thermal conductivity insulation composite material according to claim 1, characterized in that: The demoulding agent is one or both of zinc stearate and ethylene bis stearic acid amide, and the mass of the demoulding agent is 3% to 5% of the mass of the homopolyoxymethylene.
7. The method for manufacturing the silicon nitride high thermal conductivity insulation composite material according to claim 1, characterized in that: In the step 2, homopolyformaldehyde, initiator, antioxidant and release agent are stirred at 30-50° C., and the silicon nitride fiber has a diameter of 5-15 microns and a length of 4-8 mm.
8. The method for manufacturing the silicon nitride high thermal conductivity insulation composite material according to claim 1, characterized in that: In the step three, the mold is preheated to a temperature of 150-175° C. and pressurized to 17-30 MPa.
9. A silicon nitride high thermal conductivity insulation composite material, characterized in that: The silicon nitride high thermal conductivity insulating composite material is manufactured by the manufacturing method of any one of claims 1 to 8.
10. The use of the silicon nitride high thermal conductivity insulation composite material according to claim 9, characterized in that: Including using silicon nitride high thermal conductivity insulation composite material to manufacture the insulation board of the bus duct connector, the bending strength of the insulation board is greater than 395MPa, and the fracture toughness is greater than 10MPa / m 0.5 , thermal conductivity>25W / m·k, volume resistivity>10 13 Ω·cm.
Citation Information
Patent Citations
A high thermal conductivity silicon nitride ceramic insulating plate and its preparation method
CN112661518B